Pre‐pregnancy obesity among immigrant and non‐immigrant women in Norway: Prevalence, trends, and subgroup variations - Roy M. Nilsen; Ragnhild B. Strandberg; Yaliso Yaya; Anne‐Siri Fismen; Ferenc Macsali; Nils‐Halvdan Morken; Francisco Gómez Real; Erica Schytt; Eline S. Vik; Linn Marie Sørbye (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study assessed prevalence and time trends of pre‐pregnancy obesity in immigrant and non‐immigrant women in Norway and explored the impact of immigrants' length of residence on pre‐pregnancy obesity prevalence. Material and Methods Observational data from the Medical Birth Registry of Norway and Statistics Norway for the years 2016–2021 were analyzed. Immigrants were categorized by their country of birth and further grouped into seven super regions defined by the Global Burden of Disease study. Pre‐pregnancy obesity was defined as a body mass index ≥30.0 kg/m2, with exceptions for certain Asian subgroups (≥27.5 kg/m2). Statistical analysis involved linear regressions for trend analyses and log‐binomial regressions for prevalence ratios (PRs). Results Among 275 609 pregnancies, 29.6% (N = 81 715) were to immigrant women. Overall, 13.6% were classified with pre‐pregnancy obesity: 11.7% among immigrants and 14.4% among non‐immigrants. Obesity prevalence increased in both immigrants and non‐immigrants during the study period, with an average yearly increase of 0.62% (95% confidence interval [CI]: 0.55, 0.70). Obesity prevalence was especially high in women from Pakistan, Chile, Somalia, Congo, Nigeria, Ghana, Sri Lanka, and India (20.3%–26.9%). Immigrant women from “Sub‐Saharan Africa” showed a strong association between longer residence length and higher obesity prevalence (≥11 years (23.1%) vs. <1 year (7.2%); adjusted PR = 2.40; 95% CI: 1.65–3.48), particularly in women from Kenya, Eritrea, and Congo. Conclusions Prevalence of maternal pre‐pregnancy obesity increased in both immigrant and non‐immigrant women from 2016 to 2021. Several immigrant subgroups displayed a considerably elevated obesity prevalence, placing them at high risk for adverse obesity‐related pregnancy outcomes. Particular attention should be directed towards women from “Sub‐Saharan Africa”, as their obesity prevalence more than doubled with longer residence.